Leveraging Regional Differences and Cross‐Border Collective Institutions: The Case of Skill Formation and Employment in the Border Region of France, Germany, and Switzerland. Issue 2 (24th February 2021) - Graf, Lukas
Abstract: European cross‐border regions often display substantial political and economic activity. A key example is the French‐German‐Swiss Upper Rhine region, where three distinct national governance models come together. In this dynamic cross‐border industry cluster, traditional political‐administrative units often do not meet the functional needs of employers and (future) employees. This comparative institutional analysis refers to Varieties of Capitalism and Local Production Systems perspectives to explore the operations of this cluster. It finds two main patterns through which education and training are embedded in the cross‐border context: on the one hand, the leveraging of distinct institutional advantages in the different parts of the region and, on the other, the creation of cross‐border collective competition goods in the form of jointly provided educational institutions. Through these two strategies, local actors within the cross‐border industry cluster can turn their peripheral location into an institutional advantage. Zusammenfassung: In europäischen Grenzregionen findet vielfach rege politische und wirtschaftliche Zusammenarbeit statt. Ein zentrales Beispiel hierfür ist die deutsch‐französisch‐schweizerische Oberrheinregion. Am Oberrhein treffen drei unterschiedliche nationale Governance‐Modelle aufeinander, wobei die jeweiligen politisch‐administrativen Strukturen oftmals nicht den funktionalen Bedürfnissen der lokalen ArbeitgeberInnen und ArbeitnehmerInnen entsprechen. Die vorliegende vergleichende Institutionenanalyse arbeitet mit dem „Varieties of Capitalism"‐Ansatz und der „Local Production Systems"‐Perspektive, um die massgeblichen Koordinationsmuster innerhalb dieses Wirtschaftsraums zu untersuchen. Es zeigt sich, dass die Akteure des Bildungssystems in zweifacher Form in den grenzüberschreitenden Kontext eingebettet sind: Einerseits durch die Nutzung der komparativ‐institutionellen Vorteile der jeweiligen Teile des Clusters und andererseits durch die Schaffung transnationaler kollektiver Wettbewerbsgüter in Form grenzüberschreitender Bildungsprogramme. Diese Einbindung ermöglicht es lokalen Akteuren, institutionelle Vorteile aus ihrer Grenzlage zu ziehen. Résumé: Les régions transfrontalières européennes présentent souvent une activité politique et économique importante. Un exemple clé est la région franco‐germano‐suisse du Rhin supérieur, où se rencontrent trois modèles différents de gouvernance nationale. Dans cette zone transfrontalière, industrielle et dynamique, les unités politico‐administratives ne répondent pas aux besoins fonctionnels des employeurs et des (futur·e·s) employé·e·s. Cette analyse comparative et institutionnelle s'appuie sur les perspectives des variétés du capitalisme et des systèmes de production locaux pour explorer les opérations de ce cluster . Elle identifie deux modèles principaux selon lesquels l'éducation et la formation s'inscrivent dans le contexte transfrontalier : d'une part, l'exploitation d'avantages institutionnels distincts dans les différentes parties du cluster et, d'autre part, la création de biens collectifs de compétition sous la forme d'établissements d'enseignement communs. Grâce à ces deux stratégies, les acteurs locaux de cette zone industrielle transfrontalière peuvent transformer leur situation périphérique en avantage institutionnel.